COMPOSITION OF THE ESSENTIAL OILS OF CALAMINTHA NEPETA (L.) SAVI SUBSP. NEPETA AND CALAMINTHA NEPETA (L.) SAVI SUBSP. GLANDULOSA (REQ.) P.W. BALL - Alan, S.; Kürkçüolu, M.; Baser, K. Hüsnü C. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
Calamintha Miller (Lamiaceae) is represented in Turkey by 9 species and 13 taxa, 6 being endemic. The rate of endemism in Turkey is over 45%. In the present study, aerial parts of the Calamintha nepeta (L.) Savi subsp. nepeta were collected from the regions of Tarsus (A), Silifke (B), Bart (C) and Calamintha nepeta (L.) Savi subsp. glandulosa (Req.) P.W. Ball collected from the regions of the Zonguldak (D) and Manisa (E). Water distilled essential oils from the aerial parts of Calamintha species from Turkey were analysed by GC and GC/MS. Trans-piperitone oxide (44.4 %) and piperitenone oxide (11.7 %) were detected as main constituents in sample A; Pulegone (11.9 %), menthone (11.9 %) and carvacrol (10.0 %) were found as main constituents in sample B; Trans-piperitone oxide ( 30.9 %), caryophyllene oxide (7.8 %) were detected as main constituents in sample C; Pulegone (19.5 %), menthone (9.7 %), caryophyllene oxide (7.9 %) and trans-piperitone oxide (5.7 %) were detected as main constituents in sample D; Trans-piperitone oxide (34.2 %), limonene (17.3 %) and piperitenone oxide (10.8 %) were found as main constituents in sample E.